N6-methyladenosine RNA is modified in the rat hippocampus following traumatic brain injury with hypothermia treatment - Cheng, Jin; Lin, Lian; Yu, Jiangtao; Zhu, Xiaolu; Ma, Haoli; Zhao, Yan (Frontiers in Neuroscience, 2023)
Recent studies have suggested a role for N6-methyladenosine (m6A) modification in neurological diseases. Hypothermia, as a commonly used treatment for traumatic brain injury, may plays a neuroprotective role by altering N6-methyladenosine (m6A) modifications. In this study, methylated RNA immunoprecipitation sequencing (MeRIP-Seq) was applied to conduct a genome-wide analysis of RNA m6A methylation in rat hippocampus of traumatic brain injury (TBI) and Post-TBI hypothermia treatment. In addition, we identified the expression of mRNA after TBI. We found 951 peaks of significant changes in the hippocampus after TBI. Moreover, a total of 758 significantly changed peaks were identified between TBI group and hypothermia treatment group. Among these differential peaks, 173 peaks were altered by TBI and reversed by hypothermia treatment, such as Plat, Pdcd5, Rnd3, Sirt1, Plaur, Runx1, Ccr1, Marveld1, Lmnb2, and Chd7. We found hypothermia treatment transformed some m6A methylation landscape of rat’s hippocampus induced by TBI.